A prospective phase II study of carboplatin and nab-paclitaxel in patients with advanced non-small cell lung cancer and concomitant interstitial lung disease (HOT1302). (December 2019) - Asahina, Hajime; Oizumi, Satoshi; Takamura, Kei; Harada, Toshiyuki; Harada, Masao; Yokouchi, Hiroshi; Kanazawa, Kenya; Fujita, Yuka; Kojima, Tetsuya; Sugaya, Fumiko; Tanaka, Hisashi; Honda, Ryoichi; et al.
Highlights: We tested nab -paclitaxel + carboplatin in patients with both advanced NSCLC and ILD. The patient' objective response rate was 56%. This therapy was as effective in patients with NSCLC and ILD as in those NSCLC alone. A phase 3 trial of this combined therapy in patients with NSCLC and ILD is warranted. Abstract: Objectives: Patients with concomitant advanced non-small cell lung cancer (NSCLC) and interstitial lung disease (ILD) are excluded from most clinical chemotherapy trials because of the high risk of exacerbating the latter condition. This study prospectively investigated the efficacy and safety of albumin-bound paclitaxel ( nab -paclitaxel) in combination with carboplatin in patients with both advanced NSCLC and ILD. Patients and methods: The enrolled patients had treatment-naïve, advanced NSCLC with ILD. Patients received 100 mg/m 2 nab -paclitaxel weekly and carboplatin at an area under the concentration-time curve of 6 once every 3 weeks for 4–6 cycles. The primary endpoint was the overall response rate (ORR); secondary endpoints included toxicity, progression-free survival (PFS), and overall survival (OS). Results: Thirty-six patients were enrolled between April 2014 and September 2017. Sixteen patients (44.4%) had adenocarcinoma, 15 (41.7%) had squamous cell carcinoma (Sq), and 5 (13.9%) had non-small cell carcinoma. The median number of cycles administered were 4 (range: 1–6). The ORR was 55.6% (95% confidence interval [CI]: 39.6–70.5). The median PFS and OS were 5.3 months (95% CI: 3.9–8.2) and 15.4 months (95% CI: 9.4–18.7), respectively. A greater proportion of patients with Sq experienced improvements than did those with non-Sq: ORRs, 66.7% (95% CI: 41.7–84.8) vs. 47.6% (95% CI: 28.3–67.6) (P = 0.254); median PFS, 8.2 months (95% CI: 4.0–10.2) vs. 4.1 months (95% CI: 3.3–5.4) (HR, 0.60 [95% CI, 0.30–1.20]; P = 0.15); and median OS, 16.8 months (95% CI: 9.8–not reached) vs. 11.9 months (95% CI: 7.3–17.4) (HR, 0.56 [95% CI, 0.24–1.28]; P = 0.17). Two patients (5.6%) experienced grade ≥2 pneumonitis and 1 patient (2.8%) died. Conclusion: Weekly nab-paclitaxel combined with carboplatin showed favorable efficacy with acceptable toxicity in patients with both advanced NSCLC and ILD.